A 6 ka BP Reconstruction for the Island of Newfoundland from a Synthesis of Holocene Lake-Sediment Pollen Records - Brown MacPherson, Joyce (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTA 6 ka reconstruction for the island of Newfoundland is presented in the context of a synthesis of Holocene pollen records for twelve sites within or at the margin of the boreal forest, five of which are new. Climatic reconstruction is based primarily on representation of the major boreal taxa: balsam fir, spruce, birch and pine, with charcoal data for some sites. The period of greatest Holocene warmth began at 6 ka. Although temperatures at inland sites were at or close to modern values as early as 8.5-8.0 ka, it was not until 6 ka on the Avalon Peninsula, in the southeast, and 5.5 ka in the north, that coastal sites registered expansion of more thermophilous taxa. Thus oceanic warming lagged terrestrial warming. Temperatures during the period of greatest warmth were no more than 1.0°C higher than modern, based on fluctuations of the upper forest limit and post-Hypsithermal contraction of the range of indicator taxa. Fire importance increased after 6 ka as pine expanded, but moisture availability also increased. The first indications of cooling occurred on the coast at 4.5-4.0 ka, but at different times after 4.0 ka inland; thus oceanic cooling led terrestrial cooling. The latest Holocene has been cool, moist and relatively free from fire.